“Depuración de los ácidos grasos saturados del aceite de palma (Elaies guineensis) para la elaboración de biodiesel como alternativa de mejor en sus propiedades de flujo a bajas temperaturas” - Leiva Piedra, Jorge Abelardo (2011)
Palm oil biodiesel has excellent properties as fuel for anginas, however associated as their chemical composition highly saturated, this biofuel presents a poor performance at temperatures close to ambient temperatures of sore cities of the Peru. 16 ºC biofuel of palm oil begins to form small crystals, which as the temperature continue to decline, accelerate their growth and will agglomerate, in such a way that at a temperature between 12 and 9 ° C can completely stop the flow of the fuel. In this work was assessed the technique of winterization oil of palm oil through crystallization induced by cooling to improve their properties of flow at low temperatures. The variables taken into account in this process were the temperature of cooling or winterization and the time of stabilization. According to the points cloud and performance of the palm oil biofuel. The process allowed to obtain a fraction liquid temperature of winterization with best point cloud at a lower temperature than the original Palm biodiesel. At tested conditions (tp = 08 hours and T = 1 O ºC) obtained a fraction liquid with a point cloud 8 º C lower than Palm oil without fractionated, also won a point cloud 8 º C lower than biodiesel made from the oil palm without winterize. Such a change in the point cloud of palm oil and biofuel produced by the above-mentioned oil is due to the increase in the content of unsaturated fatty acids in its structure. Finally, we can conclude that it was possible to improve the quality of biodiesel made from oils winterize, in terms of point cloud and the control sample had a value of 13 º C point cloud compared this with the treatment ' by 08 hours at 10 º C where it was reduced to 5 ºC.